Evaluation of the AnaeroPack Campylo System for Growth of Microaerophilic Bacteria - Van Horn, Kenneth (American Society for Microbiology, 1999)
Growth of microaerophilic bacteria in the AnaeroPack Campylo (Mitsubishi Gas Chemical America, Inc., New York, N.Y.) atmosphere generation system was compared to growth in the CampyPak Plus jar and CampyPak pouch (Becton-Dickinson Microbiology Systems [BDMS], Cockeysville, Md.). Growth in the AnaeroPack Campylo system was considered equivalent to or better than growth obtained in the CampyPak Plus and CampyPak pouch systems for 48 of the 50 Helicobacter pylori strains and for all 28 Campylobacter species tested. All of the 78 organisms tested were recovered in each system in equivalent colony counts. Two strains of H. pylori grown in the AnaeroPack Campylo system were observed to have colony morphology growth discrepancies when compared to growth in the two BDMS systems. Atmosphere failure with the AnaeroPack Campylo was not detected with Campylobacter jejuni ATCC 33291 used as a growth control. The AnaeroPack Campylo system is easy to use and supports the growth of campylobacters and H. pylori.